Appendicitis-Like Picture Induced by Foreign Body in a 2-Year-Old Boy - Sadi A. Abukhalaf; Rami A. Misk; Hussam I. Alzeerelhouseini; Ismaeel M. Irziqat; Abdulrahman H. Asaferah; Osama Y. Aljabarein; Khalil N. Abuzaina (Case Reports in Surgery)
Background and Aim. Appendicitis is unusual in toddlers and foreign body- (FB-) induced appendicitis is rare. We present a FB-induced appendicitis in a toddler with no suggestive history of FB ingestion. Case Presentation. A 2-year-old healthy boy presented to the emergency department with irritability for 3 days duration associated with fever of 39°C, nausea, anorexia, and vomiting. There was no history of foreign body ingestion. The abdomen was distended and diffusely tender. An abdominal ultrasound (US) was suggestive of perforated appendicitis with appendicular mass formation. An abdominal X-ray showed a pin-like foreign body in the abdomen. An emergent appendectomy was performed. Intraoperatively, a sealed small cecal perforation was noticed. A 5 cm pin-like metallic foreign body was found to obstruct the appendicular lumen. The appendix was grossly normal without inflammatory changes. Conclusion. FB-induced perforations or appendicitis albeit in patients with no history of FB ingestion or infants and toddlers need a high clinical suspicion to prevent the delay in diagnosis and the subsequent complications.